The criminalization of funk dance and rap and the black genocide in the cities of Rio de Janeiro and Lisbon - Pereira de Araujo, Danielle (2024)
This work reflects on the criminalization of baile funk and rap in the Brazilian and Portuguese contexts. We are interested in reflecting on the historical, political and institutional conditions that normalize a regime of permanent exception to which the police and the justice system subject racialized people and their forms of artistic expression. The criminalization of art produced by the black community has served to associate race, territory and danger and to delegitimize artistic manifestations that denounce the practices of daily racism experienced by that community. The criminalization of baile funk and rap leads us to problematize the terms in which white scholars discuss security policies for black youth and favelas. In addition, it becomes imperative to qualify the debate about citizenship. The black movement challenges this grammar and places the existence of institutional racism at the heart of the discussion on the criminalization of black youth.